GAMBARAN SEROLOGIS IgM – IgG CEPAT DAN HEMATOLOGI RUTIN PENDERITA DBD - D. Irwadi; M. Arif; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
The prevalence of Dengue Hemorrhagic Fever (DHF) in South Sulawesi is still high. Proper and immediate management is importantto reduce the disease morbidity and mortality The aims of this study are to know the between correlate in stages of the disease and valuesof blood IgM-IgG, routine haematology analyses as will as infection status. A cross sectional study was done at Wahidin SudirohusodoHospital Makassar in January – June 2006. The diagnosis of DHF following WHO criteria (1999) and Immunocromatographic unit(ICT) for sera IgM-IGg have been conducted. From 83 collected samples, 37 male (44.6%) and female 46 (55.4%) ranged betweenage 6 months up to 47 year old. The decrease of trombocyte counts (mean 70.120/μL) and increase of (mean 10.09%) were observed.Serological unit result showed 10 (12%) primary infections and 68 (82%) secondary infections. Immunoglobulin G could be detectedin the second day of fever. The samples, 56 (67.5%) were stage I, 15 (18.1%) were stage II, and 12 (14.4%) were stage III or IV, thatmeans there were correlation between infection status and disease’s stages (p<0.01). It can be concluded they routine blood analysisis still useful for diagnosis of DHF, because it was confirmed by rapid serological unit specifically for IgM-IgG in early phase of DHF. Sothey an adequate treatment came out in order to prevent severe case of the disease.